Coming of Age: Affiliate Member Profile and Participation in the Annual Scientific Meeting of the Cardiac Society of Australia and New Zealand - Astley, C.; Portelli, L.; Whalley, G.; Davidson, Patricia (Elsevier, 2007)
Background: Nursing, allied health and technical personnel are increasingly being recognised as pivotal in the diagnosis and management of heart disease. This recognition is mirrored in research, scholarship and professional development activities. Documenting the evolution and progression of a group’s professional development is a useful strategy in informing future strategic initiatives. Aim: The purpose of this paper is to illustrate the development and participation of the Affiliates group within the Cardiac Society of Australia and New Zealand (CSANZ). Method: Data related to CSANZ membership, participation in the Annual Scientific Meeting as well as the number, type and ranking of abstracts were retrieved from CSANZ records for the period 1995–2003. These data were analysed using descriptive statistics. Results: Since the introduction of the Affiliate member status in 1988, membership has grown steadily, as has participation of members in the governance of the CSANZ. Mean abstract grades of Affiliate members are increasingly comparable with those of the FCSANZ, Ordinary and Associate members. Conclusions: Affiliate members are increasing their profile in the highly competitive environment of the Annual Scientific Meeting, demonstrating the critical role of nursing, allied health and technical professions in cardiovascular health and science.